Provisioning SQL databases exam 70-765 certification training prepare for the Microsoft 70-765 exam and work towards your MCSA : SQL 2016 database administration certification - Long, Mark (O'Reilly, 2017)
"Microsoft exam 70-765 (aka "Provisioning SQL Databases") is one of two tests you must pass to earn a Microsoft Certified Solutions Associate (MCSA): 2016 Database Administration certification. This course supplies you with the knowledge you need to pass the 70-765. It's also a practical introduction to Microsoft's Azure cloud platform service. It covers the processes, implications, technologies, and actions involved in utilizing SQL Server in the cloud in both PaaS and IaaS environments. After you learn how to create and use a free Microsoft Azure subscription, you will get hands-on experience with SQL Server in various cloud-based configurations, giving you an understanding of the implications and purposes for various options."--Resource description page
Title from title screen (viewed September 22, 2017). - Date of publication from resource description page
Keywords: SQL server -- Study guides -- Examinations; Client/server computing -- Study guides -- Examinations; Electronic data processing personnel -- Study guides -- Certification; Database management -- Study guides -- Examinations; SQL server; Architecture client-serveur (Informatique); Examens; Guides de l'étudiant; Bases de données; Gestion; Examens; Guides de l'étudiant; Client/server computing; Examinations; Database management; Examinations; Electronic data processing personnel; Certification; Examinations; examination study guides; Study guides; Guides de l'étudiant